ANALISIS PENGARUH PERTUMBUHAN EKONOMI YANG MENUNJANG PENERIMAAN PAJAK PENGHASILAN DI PROVINSI JAMBI - Afrizal - (JURNAL AKADEMIKA)
Income tax where the size of the economic growth that is marked by changes in per capita income ofthe society also influence the size of the income tax revenue. Income tax imposed itself on the basis of the amount of income is lacking average taxpayer - average overthe period 2002 - 2011 income tax revenue in Jambi province has increased the average - average of 15.95 percent. This growth rate is a high rate. In the same period GDP growth in 2002 is based haraga constant at 5.95 percent